Two metallocarboxypeptidase inhibitors are implicated in tomato fruit development and regulated by the Inner No Outer transcription factor. (January 2018) - Molesini, B.; Rotino, G.L.; Dusi, V.; Chignola, R.; Sala, T.; Mennella, G.; Francese, G.; Pandolfini, T.
Highlights: Metallocarboxypeptidase inhibitors sequentially expressed during fruit development. Involvement of metallocarboxypeptidase inhibitors in fruit setting. Coordinated control of metallocarboxypeptidase inhibitors by Inner No Outer. Abstract: The TCMP-1 and TCMP-2 genes of tomato code for metallocarboxypeptidase inhibitors and show sequential, tightly regulated expression patterns during flower and fruit development. In particular, TCMP-1 is highly expressed in flower buds before anthesis, while TCMP-2 in ripe fruits. Their expression pattern suggests that they might play a role in fruit development. Here, to investigate their function, we altered their endogenous levels by generating transgenic plants harbouring a chimeric gene expressing the TCMP-1 coding sequence under the control of the TCMP-2 promoter. The expression of the transgene caused an earlier fruit setting with no visible phenotypic effects on plant and fruit growth. The altered TCMP-1 regulation determines an increased level of TCMP-1 in the fruit and unexpected changes in the levels of both TCMPs in flower buds before anthesis, suggesting a mechanism of transcriptional cross-regulation. We in silico analysed TCMPs promoter regions for the presence of common cis acting elements related to ovary/fruit development and we found that both promoters contain putative binding sites for INNER NO OUTER (INO), a transcription factor implicated in ovule development. By chromatin immunoprecipitation, we proved that INO binds to TCMP-1 and TCMP-2 promoters, thereby representing a candidate regulatory factor for coordinated control of TCMPs .